Mitochondria in COVID-19: from cellular and molecular perspective - Rurek, Michał (Frontiers in Physiology, 2024)
The rapid development of the COVID-19 pandemic resulted in a closer analysis of cell functioning during -coronavirus infection. This review will describe evidence for COVID-19 as a syndrome with a strong, albeit still underestimated, mitochondrial component. Due to the sensitivity of host mitochondria to coronavirus infection, SARS-CoV-2 affects mitochondrial signaling, modulates the immune response, modifies cellular energy metabolism, induces apoptosis and ageing, worsening COVID-19 symptoms which can sometimes be fatal. Various aberrations across human systems and tissues and their relationships with mitochondria were reported. In this review, particular attention is given to characterization of multiple alterations in gene expression pattern and mitochondrial metabolism in COVID-19; the complexity of interactions between SARS-CoV-2 and mitochondrial proteins is presented. The participation of mitogenome fragments in cell signaling and the occurrence of SARS-CoV-2 subgenomic RNA within membranous compartments, including mitochondria is widely discussed. As SARS-CoV-2 severely affects the quality system of mitochondria, the cellular background for aberrations in mitochondrial dynamics in COVID-19 is additionally characterized. Finally, perspectives on the mitigation of COVID-19 symptoms by affecting mitochondrial biogenesis by numerous compounds and therapeutic treatments are briefly outlined.